2020
DOI: 10.1055/a-1194-5381
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Care in Nursing Homes for the Blind: A Growing Challenge

Abstract: Background The demographic change in Germany will lead to an increase in irreversible age-related eye diseases. This will increase the need for specialised care facilities for visually impaired people. Due to reduced mobility, residents in such facilities often do not receive adequate ophthalmological care. New concepts must therefore be considered for this group of patients. One approach is to set up an ophthalmological examination unit within the facility combined with regular visits by an ophthalmologist. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“… 20 For family members and caregivers, it will lead to physical and mental diseases 21 and increase the risk of anxiety and depression. 22 Patients with VI will also cause a substantial financial burden to society; for example, they are more inclined to live in nursing institutions 23 and are more likely to move into nursing institutions in advance, 24 which increases the burden on nursing institutions. Previous studies have shown that VI also poses a substantial financial burden to the world.…”
Section: Introductionmentioning
confidence: 99%
“… 20 For family members and caregivers, it will lead to physical and mental diseases 21 and increase the risk of anxiety and depression. 22 Patients with VI will also cause a substantial financial burden to society; for example, they are more inclined to live in nursing institutions 23 and are more likely to move into nursing institutions in advance, 24 which increases the burden on nursing institutions. Previous studies have shown that VI also poses a substantial financial burden to the world.…”
Section: Introductionmentioning
confidence: 99%
“…For family members and caregivers, it will lead to physical and mental diseases [21]and increase the risk of anxiety and depression [22]. Patients with VI will also cause a substantial nancial burden to society; for example, they are more inclined to live in nursing institutions [23] and are more likely to move into nursing institutions in advance [24], which increases the burden on nursing institutions. Previous studies have shown that VI also poses a substantial nancial burden to the world [25,26].…”
Section: Introductionmentioning
confidence: 99%